Analysis of factors influencing farmers’ decision to continue herbal plant farming in Pace Village, Silo District, Jember Regency - Eliyatiningsih, Eliyatiningsih; Erdiansyah, Iqbal; Sari, Vega Kartika; Nurahmanto, Dwi (International Integrated Agricultural Journal (IIAJ), 2025)
Pace Village, Silo District, is a center for herbal plant production and is the largest ginger producer in Jember Regency. Farmers in the area have been cultivated various herbal plants for the past five years, both as main plants in their yards and as intercrops in addition to coffee plants. The outbreak of Covid 19 in 2019 has had a positive impact on herbal plant farmers in Pace Village because the demand and sales of herbal medicines have increased sharply. This study aims to determine the factors that influence farmers' decisions to continue herbal farming in Pace Village, Silo District, Jember Regency. The determination of the research location was carried out by purposive sampling and the respondents of this study were 35 farmers who cultivate herbal plant. The data analysis technique used was logistic regression with the help of the IBM SPSS 22 program. The results showed that the factors that influenced the probability of farmers continuing herbal plant farming were age, land area, farming experience, motivation, and membership in farmer groups. Based on the research results, it is recommended that the government support the development of herbal farming in Pace Village so that it becomes the main farming business that can provide optimal benefits for farmers.